2017
DOI: 10.1038/s41564-017-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

A plasmid from an Antarctic haloarchaeon uses specialized membrane vesicles to disseminate and infect plasmid-free cells

Abstract: The major difference between viruses and plasmids is the mechanism of transferring their genomic information between host cells. Here, we describe the archaeal plasmid pR1SE from an Antarctic species of haloarchaea that transfers via a mechanism similar to a virus. pR1SE encodes proteins that are found in regularly shaped membrane vesicles, and the vesicles enclose the plasmid DNA. The released vesicles are capable of infecting a plasmid-free strain, which then gains the ability to produce plasmid-containing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(170 citation statements)
references
References 63 publications
8
162
0
Order By: Relevance
“…The non‐lytic pleomorphic virus life cycle starts with fusion between the viral and host membranes and they exit the host cell most probably by budding, preserving the host membrane integrity (Svirskaite et al ., ; El Omari et al ., ). Their simplistic mechanism of nucleic acid transmission resembles the function of the recently described ‘infectious’ plasmid membrane vesicles isolated from Antarctic species of haloarchaea (Erdmann et al ., ), supporting the tight evolutionary relationships between viruses and non‐viral mobile genetic elements (Iranzo et al ., ). Pleolipoviruses share a conserved core of four to five genes, mainly encoding major structural proteins of which one is the spike protein responsible for host attachment and membrane fusion (Pietilä et al ., ; Sencilo et al ., ; El Omari et al ., ).…”
Section: Introductionmentioning
confidence: 62%
“…The non‐lytic pleomorphic virus life cycle starts with fusion between the viral and host membranes and they exit the host cell most probably by budding, preserving the host membrane integrity (Svirskaite et al ., ; El Omari et al ., ). Their simplistic mechanism of nucleic acid transmission resembles the function of the recently described ‘infectious’ plasmid membrane vesicles isolated from Antarctic species of haloarchaea (Erdmann et al ., ), supporting the tight evolutionary relationships between viruses and non‐viral mobile genetic elements (Iranzo et al ., ). Pleolipoviruses share a conserved core of four to five genes, mainly encoding major structural proteins of which one is the spike protein responsible for host attachment and membrane fusion (Pietilä et al ., ; Sencilo et al ., ; El Omari et al ., ).…”
Section: Introductionmentioning
confidence: 62%
“…The genetic organization of pT26‐2 is reminiscent of that of the infectious plasmid pR1SE recently isolated from vesicles of the halophilic archaeon Halorubrum lacusprofundi R1SE, albeit without any direct sequence conservation (Erdmann et al ., ). It was experimentally shown that pR1SE can promote its own transfer between cells via extracellular vesicles which contain multiple transmembrane proteins encoded by the plasmid itself (Erdmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The genetic organization of pT26‐2 is reminiscent of that of the infectious plasmid pR1SE recently isolated from vesicles of the halophilic archaeon Halorubrum lacusprofundi R1SE, albeit without any direct sequence conservation (Erdmann et al ., ). It was experimentally shown that pR1SE can promote its own transfer between cells via extracellular vesicles which contain multiple transmembrane proteins encoded by the plasmid itself (Erdmann et al ., ). Other plasmids in Thermococcales species, such as the pTN3, have been shown to use membrane vesicles to transfer horizontally (Gaudin et al ., ), and two species containing integrated plasmids of the pT26‐2 family, Thermococcus gammatolerans and Pyrococcus horikoshii , were shown to produce membrane vesicles containing cellular DNA (Soler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Cytoskeletal proteins often have multiple functions, and are adapted for use in various biological contexts. A recent study analysing the composition of membrane vesicles (MVs) of a haloarchaeal species, Halorubrum lacusprofundi, revealed the presence of a CetZ1 homolog in MVs and specialised plasmid-containing membrane vesicles (PVs) [47]. This protein was significantly more enriched in purified vesicles when compared with membrane fractions prepared from the host, suggesting that it might play a role in membrane vesicle formation or structure [47].…”
Section: Expression Of a Cetz1mentioning
confidence: 99%